THE EFFECT OF HOMESCOOLING ON COGNITIVE DEVELOPMENT AND LEARNING MOTIVATION PARTICIPANTS (Case Study in One Family Applying Homescooling) - Dewi Safitri Elshap (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
The family is the first and primary school to provide education to their children. Students who are highly motivated in learning will likely gain high learning results as well, meaning that the higher the motivation, the more intensity of effort and effort made, the higher the learning achievement it earns. One method that can be applied by parents is the method of homeschooling. Parents and tutors who provide education to learners. Homeschooling education is more flexible and time-bound as in formal schools. The purpose of this study is to examine the effect of homeschooling on cognitive development and learning motivation and to know the learning outcomes obtained by children through homeschooling program. This research is a qualitative research case study. One family research informant, with parents primary informant, and child supporting informant, and teacher. This research instrument includes test (description problem) and non test (attitude scale). Data were obtained through interviews and participant observation of the family. The data is then processed using theme analysis. The results that can be obtained from this research is increased student achievement and good learning motivation. homeschooling positively affects both academic and non-academic abilities of children.